2018
DOI: 10.3390/metabo8010024
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an Epoxide Metabolite of Lycopene in Human Plasma Using 13C-Labeling and QTOF-MS

Abstract: The carotenoid lycopene is a bioactive component of tomatoes and is hypothesized to reduce risk of several chronic diseases, such as prostate cancer. The metabolism of lycopene is only beginning to be understood and some studies suggest that metabolites of lycopene may be partially responsible for bioactivity associated with the parent compound. The detection and characterization of these compounds in vivo is an important step in understanding lycopene bioactivity. The metabolism of lycopene likely involves bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 43 publications
2
5
0
Order By: Relevance
“…As reviewed above, Moran found a higher turnover rate of absorbed all-trans lycopene compared to cislycopene, suggesting that there may be differential degradation or metabolism of the different isomers within body tissues and that trans-to-cis isomerization may occur. Further analyses of serum samples from Moran et al were performed by Cichon et al and a 1,2 lycopene epoxide was found in plasma beginning 2-4 h post-dosing and represented 1.7% of the dose [97]. This work supports previous work by Khachik et al, who enrolled three lactating women one month postpartum and analyzed breastmilk and serum for carotenoids [98].…”
Section: Excretionsupporting
confidence: 73%
See 1 more Smart Citation
“…As reviewed above, Moran found a higher turnover rate of absorbed all-trans lycopene compared to cislycopene, suggesting that there may be differential degradation or metabolism of the different isomers within body tissues and that trans-to-cis isomerization may occur. Further analyses of serum samples from Moran et al were performed by Cichon et al and a 1,2 lycopene epoxide was found in plasma beginning 2-4 h post-dosing and represented 1.7% of the dose [97]. This work supports previous work by Khachik et al, who enrolled three lactating women one month postpartum and analyzed breastmilk and serum for carotenoids [98].…”
Section: Excretionsupporting
confidence: 73%
“…Isotopically labeled carotenoids are an effective way of investigating lycopene excretion in vivo. Such studies have been carried out using lycopene with rats, gerbils, and humans [92,[95][96][97]. One study used F344 male rats that were fed an AIN-93G diet enriched with lycopene (25 mg per kg diet) [95].…”
Section: Excretionmentioning
confidence: 99%
“…Its expression by human intestinal cells further supports the hypothesis that it may act during digestion . Indeed, LYC metabolites have been found circulating in human plasma, although the origin of these metabolites has not been established.…”
Section: Introductionsupporting
confidence: 53%
“…Also, this study was conducted in healthy male subjects, and differences could be observed in other demographic groups. Finally, only apo‐lycopenoids (i.e., <40 carbon metabolites) were studied in this work, to the exclusion of other reported LYC epoxides and diols, which have been previously examined …”
Section: Discussionmentioning
confidence: 99%
“…Some studies suggest that metabolites of lycopene may play a role in the biological activities of lycopene. However, only a limited number of studies have investigated the role of lycopene metabolites in vivo [ 128 , 129 , 130 , 131 , 132 ].…”
Section: Carotenoid Lycopene: Chemistry and Its Isomersmentioning
confidence: 99%